2009
DOI: 10.1038/ki.2008.638
|View full text |Cite
|
Sign up to set email alerts
|

Factors other than glomerular filtration rate affect serum cystatin C levels

Abstract: Cystatin C is gaining acceptance as an endogenous filtration marker. Factors other than glomerular filtration rate (GFR) that affect the serum level have not been carefully studied. In a cross-sectional analysis of a pooled dataset of participants from clinical trials and a clinical population with chronic kidney disease (N=3418), we related serum levels of cystatin C and creatinine to clinical and biochemical variables after adjustment for GFR using errors-in-variables models to account for GFR measurement er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
501
7
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 655 publications
(547 citation statements)
references
References 32 publications
19
501
7
20
Order By: Relevance
“…For example, it is now well recognized that there are many factors associated with the serum level of cystatin C other than GFR, but the mechanisms for these associations are not well understood. 11 …”
Section: Non-gfr Determinants Of Serum Levels Of Endogenous Filtratiomentioning
confidence: 99%
“…For example, it is now well recognized that there are many factors associated with the serum level of cystatin C other than GFR, but the mechanisms for these associations are not well understood. 11 …”
Section: Non-gfr Determinants Of Serum Levels Of Endogenous Filtratiomentioning
confidence: 99%
“…2,34-35 Stevens et al found a stronger association of sCreat rather than sCysC with surrogates of muscle mass, including age, sex, race, and urine creatinine. 36 This reflects smaller contribution of muscle mass to generation of CysC than creatinine. Table 2 leVels of sCreat anD sCysC aCCorDing to the groUps of patients that reCeiVeD higher anD loWer Doses of CortiCosteroiDs * Mean ± SD, ** Median.…”
Section: Discussionmentioning
confidence: 99%
“…2,34-35 Stevens et al found a stronger association of sCreat rather than sCysC with surrogates of muscle mass, including age, sex, race, and urine creatinine. 36 This reflects smaller contribution of muscle mass to generation of CysC than creatinine. …”
mentioning
confidence: 99%
“…2005-ben hasonló megállapításo-kat tett egy szintén összefoglaló tanulmány [16]. Később több tanulmány is azt taglalta -az előzőekkel ellentét-ben -, hogy a szintje függ a kortól, nemtől, rassztól, izomtömegtől, testtömegindextől, CRP-szinttől, dohányzástól, a meghatározás módjától és még egyéb té-nyezőktől [17,18]. Nem egységes a cisztatin-C egyénen belüli biológiai változatosságának a megítélése sem.…”
Section: Megbeszélésunclassified